2001
DOI: 10.1021/ol016969p
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Pd Catalyst with tropos Biphenylphosphine (BIPHEP) Ligand by DM-DABN:  Asymmetric Catalysis by an Enantiopure BIPHEP−Pd Complex1

Abstract: [reaction: see text] The racemic Pd complex with the chirally flexible (tropos) biphenylphosphine (BIPHEP) ligand can be resolved with enantiopure 3,3'-dimethyl-2,2'-diamino-1,1'-binaphthyl (DM-DABN) as a resolving agent at room temperature. The enantiopure BIPHEP-Pd complex is obtained from complexation with enantiopure DABN followed by tropo-inversion into the single BIPHEP-Pd diastereomer at 80 degrees C and protonation at 0 degrees C. The enantiopure BIPHEP-Pd complex can be used as an efficient Lewis acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…Mikami has performed dynamic resolutions of BIPHEP on Ru [28,29], Pd [30,31], and most recently Rh [32] with the use of enantiopure chiral diamine ligands. As the barriers to atropisomerization are generally higher when BIPHEP is complexed to a transition metal, these complexes can sometimes be used for asymmetric catalysis without significant erosion of the enantiopurity of the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Mikami has performed dynamic resolutions of BIPHEP on Ru [28,29], Pd [30,31], and most recently Rh [32] with the use of enantiopure chiral diamine ligands. As the barriers to atropisomerization are generally higher when BIPHEP is complexed to a transition metal, these complexes can sometimes be used for asymmetric catalysis without significant erosion of the enantiopurity of the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…5 The complex has two biphep–Pd units in which the phenyl groups adopt either axial or equatorial orientations (Figure 1 b). The biphep portions of the tetraphos–Pd complex are quite similar not only to the biphep–Pd complex but also to many binap–metal complexes 4d. 6 In Figure 1, the axial chirality is S,S and the helical chirality is P (plus), that is, clockwise around the helix axis.…”
Section: Methodsmentioning
confidence: 76%
“…Under the same conditions, the combination of biphep–Pd complex (±)‐ 3 and 1 equivalent of ( S )‐dm‐dabn gave the single diastereomer ( S )‐ 4 through isomerization of ( R )‐ 3 at 80 °C within a shorter period of time (Scheme ) 4d. It was therefore clear that tetraphos–Pd complex 1 changes its conformation much less readily than biphep–Pd complex 3 .…”
Section: Methodsmentioning
confidence: 93%
“…In this context, we came across the reaction between HCl and [Ir( 4 -1,5-C 8 H 12 )(rac-biphep)]BF 4 , where rac-biphep is racemic 2,2 0 -bis(diphenylphosphino)-1,1 0 -biphenyl, a binaplike chelate ligand which, because of its chiral flexibility, cannot be obtained as resolved enantiomers but can adopt stereochemically robust atropisomeric conformations in metal complexes bearing enantiopure coligands (Becker et al, 2001;Korenaga et al, 2001;Mikami et al, 2001Mikami et al, , 2002Mikami et al, , 2004Mikami et al, , 2005a. As anticipated, bimetallic [Ir 2 (-Cl) 3 H 2 (biphep) 2 ]BF 4 was isolated from the reaction solution.…”
Section: Commentmentioning
confidence: 99%
“…1. While a few structural studies of biphep complexes of Ru, Rh, Pd and Pt have been reported in recent years (Becker et al, 2001;Doherty et al, 2005;Korenaga et al, 2001;Mikami et al, 2001Mikami et al, , 2002Mikami et al, , 2004Mikami et al, , 2005aOsawara et al, 2000), the title compound appears to be the first crystallographically characterized example with iridium as the central metal (Cambridge Structural Database, Version 5.28; Allen, 2002).…”
Section: Commentmentioning
confidence: 99%